Daily life during the Indian Mutiny : personal experiences of 1857 - Sherer, John Walter (An eyewitness account of the great Indian mutiny ;, 1974)
Narrative about the 1857 struggle for Indian independence by a judicial officer; previously published in F.C. Maude's Memories of the mutiny, 1894.